Identifying and developing maize germplasm with resistance to accumulation of aflatoxins - Williams, W.P.; Krakowsky, M.D.; Scully, B.T.; Brown, R.L.; Menkir, A.; Warburton, Marilyn L.; Windham, G.L. (Wageningen University & Research, 2015)
Efforts to identify maize germplasm with resistance to Aspergillus flavus infection and subsequent accumulation of aflatoxins were initiated by the US Department of Agriculture, Agricultural Research Service at several locations in the late 1970s and early 1980s. Research units at four locations in the south-eastern USA are currently engaged in identification and development of maize germplasm with resistance to A. flavus infection and accumulation of aflatoxins. The Corn Host Plant Resistance Research Unit, Mississippi State, MS, developed procedures for screening germplasm for resistance to A. flavus infection and accumulation of aflatoxins. Mp313E, released in 1990, was the first line released as a source of resistance to A. flavus infection. Subsequently, germplasm lines Mp420, Mp715, Mp717, Mp718, and Mp719 were released as additional sources of resistance. Quantitative trait loci associated with resistance have also been identified in four bi-parental populations. The Crop Protection and Management Research Unit and Crop Genetics and Breeding Research Unit, Tifton, GA, created a breeding population GT-MAS:gk. GT601, GT602, and GT603 were developed from GT-MAS:gk. The Food and Feed Safety Research Unit, New Orleans, LA, in collaboration with the International Institute for Tropical Agriculture used a kernel screening assay to screen germplasm and develop six germplasm lines with resistance to aflatoxins. The Plant Science Research Unit, Raleigh, NC, through the Germplasm Enhancement of Maize (GEM) Project provides to co-operators diverse germplasm that is a valuable source of resistance to A. flavus infection and accumulation of aflatoxins in maize